KINERJA USAHA DALAM PERIKANAN TANGKAP JARING PURSE SEINE - Herna Octivia Damayanti (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
The research objective was to analyze : (1) R/C ratio; (2) production factors; (3) return to scale; and (4) the efficiency level of capture fisheries business of Purse Seine nets. Sampling is simple random sampling with 56 Purse Seine fishermen samples. Data analysis: (a) Revenue-Cost Ratio (R/C Ratio) and (b) Stochastic Frontier Production Function. Research results: (1) R/C ratio > 1, feasible to run. (2) 99% significant production factors, namely GT boats, diesel fuel, oil, consumption and the number of crew members. 95% significant production factors, namelylarge of the net and the number of lights. (3) Return to Scale 1.276 means increasing return to scale. (4) The level of efficiency shows inefficient. Research recommendations are (1) regulations (in the form of local regulations) need to be made to control and limit fishing efforts. (2) There is a need for training on business management so that fisheries businesses, especially purse seine nets, can conduct their business professionally and efficiently. Keywords: efficiency, frontier, purse seine, R/C ratio, return to scale